(untitled) (Colombia Medica, 1990)
This paper reports two cases and reviews the literature on gastrocolic fistula complicating benign gastric ulcers. This brings the reported number of cases to 110. The pathophysiology, clinical presentation, and treatment approaches to this extremely rare complication are discussed. The most commonly used treatment is surgical en-bloc removal of the involved stomach and colon and primary reestablishment of gastrointestinal continuity.